The Dulles Corridor Metrorail Project—Extension to Dulles International Airport and Its Tunneling Aspects - J. Rudolf; V. Gall (Society for Mining, Metallurgy & Exploration, 2007)
The Virginia Department of Rail and Public Transportation and the Metropolitan Washington Airports Authority are undertaking the extension of Washington Metropolitan Area Transit Authority’s Metrorail service to Washington Dulles International Airport and beyond to Route 772 in Loudoun County, Virginia. The roughly 37 kilometers long, double track alignment involves two 700 meters long single track, soft ground NATM tunnels at Tysons Corner, two 3.3 kilometers long single track rock TBM tunnels at Dulles Airport and one 25-meter deep station at the airport to be constructed by NATM in sedimentary rock. The design-build project is being implemented in a Public-Private-Partnership. A joint venture of Bechtel and Washington Group International has concluded the preliminary engineering and construction is scheduled to start in late 2007.